The Effectiveness of A Multiple Representation-Based Flipbook to Improve Students’ Problem-Solving Ability on The Topic of Wave - Bunga Lili Annisa; Sarah Miriam; Suyidno Suyidno (Department of Physics Education, Universitas Mataram, 2022)
Flipbook with multiple representation designed through flip pdf professional software to improve problem-solving ability is still unavailable. Therefore, this study aimed to analyze the effectiveness of a Multiple Representation-Based Flipbook (MRBF) in enhancing students' problem-solving skills on the topic of waves. This research uses the ADDIE development model with 32 students of XI MIPA of one senior high school in Banjarmasin, South Kalimantan, Indonesia, as its subject of study. The data were collected through a problem-solving test to measure the indicators of visualizing problems, presenting, planning problem solving, implementing, and evaluating solutions. The results showed that the average value of students' problem-solving before and after the MRBF was applied increased from very poor to very good. In addition, the Wilcoxon test results obtained a Sig (2-tailed) value of 0.00 < 0.05 which means that the increase was significant. It was concluded that MRBF effectively improves students' problem-solving abilities in learning physics.